The Practice of Mbaranggawe Puputan : A Solution for ‎Marriage Reception in Javanese Communities During the ‎Covid - 19 Pandemic - Latifah, Anisatul (Veteran Law Review, 2021)
Javanese people are among those who always try to uphold the values of traditional and cultural traditions so that their life in the universe is always in harmony and harmony. One of the traditional traditions of the Javanese people in pursuing their life cycle in order to obtain peace of life, serenity, harmony and harmony with the universe is by carrying out certain ceremonies or customs. Examples of the traditional ceremony on the Java community is mbaranggawe pengantenan (weddings) and mbaranggawe muputi or puputan (ceremony performed after dropping the baby’s navel). The implementation of this traditional ceremony requires the involvement of many sanak sedulur (relatives) and tonggo teparo (neighborhood) owner of the ceremony. The influence of the demands of the times is felt today with the corona virus outbreak that emerged at the end of 2019 which attacked human health. This outbreak is known as Covid-19. The implementation of traditional ceremonies is very strict with the rules of its activities, which include the limited number of participants, the implementation time and the location zone that will be used in the event. With this rule, traditional ceremonial activities that are considered sacred are still carried out even though they are simple.